MODELO DE USO E OCUPAÇÃO DA PAISAGEM NO MUNICÍPIO DE GARANHUNS-PE - Melo, Felippe Pessoa de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707857 With the grant was made a geoprocessing cartographic mapping of the geographical space of Garanhuns-PE, which was aimed at understanding the current spatial configuration of the landscape and its correlations with environmental degradation. Based on information from the office and field, was to identify which space is organized in an unsustainable manner. Soon there few preserved green areas within the city limits, the area of urban expansion is advanced into the valleys, flora remaining outside the urban landscape is of secondary forest and is being minimized because of the expansion of grazing and subsistence activities.